2017
DOI: 10.1111/opo.12388
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and predictors of depressive and anxiety symptoms in older adults with vision impairment: a longitudinal prospective cohort study

Abstract: This study shows that the incidence of subthreshold depression and anxiety in older adults with vision impairment is twice as high compared with older adults in general and confirms that depression and anxiety symptoms fluctuate over time. It is of great importance that low vision rehabilitation staff monitor older adults with vision impairment who are most vulnerable for developing these symptoms, based on the risk factors that were found in this study, to be able to offer early interventions to prevent and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
80
4
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 55 publications
9
80
4
9
Order By: Relevance
“…In apparent contrast to results from previous cross-sectional (10,76) and longitudinal studies (60,77), an association between vision loss and anxiety was not found. A recent longitudinal cohort study in older adults (n=7584) by Frank et al also found no association between self-reported visual impairment and anxiety (64).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In apparent contrast to results from previous cross-sectional (10,76) and longitudinal studies (60,77), an association between vision loss and anxiety was not found. A recent longitudinal cohort study in older adults (n=7584) by Frank et al also found no association between self-reported visual impairment and anxiety (64).…”
Section: Discussioncontrasting
confidence: 99%
“…Visual impairment was found to be associated with depression over time. Previous longitudinal studies reported con icting results: some found an association between visual impairment and the development of depression (13,(60)(61)(62)(63)(64)(65), while others did not (66,67). We provide additional evidence based on a large sample and longitudinal follow-up supporting the hypothesis that visual impairment predicts depression.…”
Section: Discussionsupporting
confidence: 51%
“…In apparent contrast to results from previous cross-sectional (10,76) and longitudinal studies (60,77), an association between vision loss and anxiety was not found. A recent longitudinal cohort study in older adults (n=7584) by Frank et al also found no association between self-reported visual impairment and anxiety (64).…”
Section: Discussioncontrasting
confidence: 99%
“…In people age 80 and older the prevalence of depression and anxiety seem to be lower than in younger age groups, ranging from 4% to 5% for depression and 1% to 3% for anxiety (21). Finally, in a recent prospective longitudinal study examining the incidence and predictors of depressive and anxiety symptoms in older adults with vision impairment, having AMD was found to be a risk factor for developing depressive symptoms (22).…”
Section: Introductionmentioning
confidence: 95%
“…Another study conducted with adults aged 55 and older found a significant association between clinical anxiety and an almost threefold increased risk of subsequent dementia(78). Finally, a longitudinal prospective study conducted with people aged 50 and older highlighted that depression and anxiety symptoms fluctuate overtime(22). According to the same study, the main risk factors for depression and anxiety include living alone, having just enough money to cover expenses, having macular degeneration, difficulties with adaptation to vision loss, reduced health related quality of life, and experiencing symptoms of anxiety / depression.…”
mentioning
confidence: 98%